Investigating Carbonaceous Aerosol and Its Absorption Properties From Fires in the Western United States (WE‐CAN) and Southern Africa (ORACLES and CLARIFY). Issue 15 (26th July 2021) - Carter, Therese S.; Heald, Colette L.; Cappa, Christopher D.; Kroll, Jesse H.; Campos, Teresa L.; Coe, Hugh; Cotterell, Michael I.; Davies, Nicholas W.; Farmer, Delphine K.; Fox, Cathyrn; Garofalo, Lauren A.; Hu, Lu; et al.
Abstract: Biomass burning (BB) produces large quantities of carbonaceous aerosol (black carbon and organic aerosol, BC and OA, respectively), which significantly degrade air quality and impact climate. BC absorbs radiation, warming the atmosphere, while OA typically scatters radiation, leading to cooling. However, some OA, termed brown carbon (BrC), also absorbs visible and near UV radiation; although, its properties are not well constrained. We explore three aircraft campaigns from important BB regions with different dominant fuel and fire types (Western Wildfire Experiment for Cloud Chemistry, Aerosol Absorption, and Nitrogen [WE‐CAN] in the western United States and ObseRvations of Aerosols above CLouds and their intEractionS and Cloud‐Aerosol‐Radiation Interactions and Forcing for Year downwind of southern Africa) and compare them with simulations from the global chemical transport model, GEOS‐Chem using GFED4s. The model generally captures the observed vertical profiles of carbonaceous BB aerosol concentrations; however, we find that BB BC emissions are underestimated in southern Africa. Our comparisons suggest that BC and/or BrC absorption is substantially higher downwind of Africa than in the western United States and, while the Saleh et al. (2014, https://doi.org/10.1038/ngeo2220 ) and FIREX parameterizations based on the BC:OA ratio improve model‐observation agreement in some regions, they do not sufficiently differentiate absorption characteristics at short wavelengths. We find that photochemical whitening substantially decreases the burden and direct radiative effect of BrC (annual mean of +0.29 W m −2 without whitening and +0.08 W m −2 with). Our comparisons suggest that whitening is required to explain WE‐CAN observations; however, the importance of whitening for African fires cannot be confirmed. Qualitative comparisons with the OMI UV aerosol index suggest our standard BrC whitening scheme may be too fast over Africa. Plain Language Summary: Smoke from fires has large air quality, health, and climate impacts. However, both the quantity of smoke and its ability to warm or cool the atmosphere remain poorly understood. The two major particle components of smoke (black carbon [BC] and organic aerosol [OA]) interact with incoming solar radiation in distinct ways, with BC generally absorbing light and leading to warming while OA mainly scatters radiation causing cooling. Some types of OA absorb over specific wavelengths of light; these particles are called brown carbon (BrC). Our work uses observations from the western United States and downwind of southern Africa and a global model to better understand the air quality and climate effects of fires in these regions. We find that BC emissions from fires are underestimated in Africa. We find that the black and/or BrC observed downwind of Africa is more absorbing than those in the western United States. We show that our current model does not accurately represent the differing observed absorption strengths for BrC. Comparing the model and observations suggests that BrC loses its ability to absorb (or whitens) in the western United States, but we cannot confirm that over Africa. Key Points: Per model‐measurement analysis, black and brown carbon (BrC) absorption efficiencies are higher in smoke from Africa relative to the western United States Modeling BrC absorption with black carbon:organic aerosol (BC:OA) parameterizations improves model‐observation agreement without sufficiently distinguishing regions A universal 1‐day BrC whitening timescale in the model performs better against observations than a scheme based on OH exposure